KEDUDUKAN SURAT KEPUTUSAN BERSAMA LEMBAGA PEMERINTAHAN DALAM SISTEM HUKUM INDONESIA (Studi: Surat Keputusan Bersama Tentang Pedoman Implementasi Undang-Undang Informasi dan Transaksi Elektronik) - M. Farhan Rynaldi; Emilda Firdaus; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The government made Law Number 11 of 2008 and then revised it with Law Number 19of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information andElectronic Transactions as a response to developments in the field of technology andinformation. This aims to fill the legal vacuum for the development of criminal acts incyberspace or social media. Meanwhile, the implementation of the Information and ElectronicTransaction Law has caused unrest in society due to the existence of several rubber articles inthe Law. So that as the government's response to this problem, the government formed a JointDecree on Guidelines for the Implementation of the Electronic Information and TransactionLaw. So with this SKB it is hoped that there will be no more multi-interpretations. However,this SKB has sparked debate in the Indonesian legal system regarding the legality of makingthe SKB as well as regarding its implementation. Because how is it possible for a legal productin the form of an Act to be locked up by an SKB as if this SKB has super power that canoverpower the Act.This type of research can be classified into the type of normative legal research relatedto the position and nature of the norms of joint decrees that are linked in the hierarchy of lawsand regulations. Then use data sources from primary, secondary and tertiary legal materialsby conducting literature studies in collecting data and using qualitative analysis methods inprocessing data and drawing conclusions.From the results of the research problem there are two main things that can beconcluded. First, the Joint Decree does not have a position in the hierarchy of Article 7 LawNumber 12 of 2011 Concerning the Formation of Legislation. Then, when viewed from Article8 Paragraph (1) regarding the Joint Decree on Government Institutions ConcerningGuidelines for the Implementation of the Information and Electronic Transactions Law, afterthe author conducted a study, it turns out that there is not a single law ordering the JointDecree to be made to the Chief of Police, Kajagung, and the Minister of Communication andInformatics as well as in terms of their authority. Second, it is necessary to review the JointDecree, because it is hoped that in the future the joint decree can become an alternative lawbefore a law is formed to overcome existing legal problems. Of course, no longer as a JointDecree but as a Joint Regulation.Keywords: Joint Decree, decision (beschikking), regulation (regeling)